Wind loads on roof-mounted isolated solar panels of tall buildings through wind tunnel testing. (1st January 2022) - Dai, S.F.; Liu, H.J.; Yang, J.H.; Peng, H.Y.
Highlights: Wind loads on isolated solar panels of tall buildings are experimentally studied. Effect of building height ( H = 24, 48, 72, and 96 m) on wind loads is examined. Buildings with lower H are likely to experience the flow reattachment over roofs. Most critical local and area-averaged negative peak loads decrease with increase of H. Buildings with lower H have enhanced flows over roofs and enlarged loads on panels. Abstract: A series of pressure tests were conducted to systematically investigate the wind loads on isolated solar panels mounted on the rooftops of tall buildings. The effects of panel location, tilt angle ( β = 15°, 30°, and 45°), and building height ( H = 24, 48, 72, and 96 m) were examined. Peak loads from taps were found two times as large as that from modules and panels. An increase in H induced a decrease in the largest mean and negative peak net panel force coefficients, which is attributed to the enhanced two-dimensionality of flows for buildings with lower heights. Specifically, the largest most critical negative peak net panel force coefficients at H = 24 m were approximately 20% larger than those at H = 96 m. Attention should be paid to wind loads on roof-mounted solar panels attached to buildings with lower heights. Besides, buildings with lower heights tend to cause more significant fluctuations of wind pressure on solar panels. Moreover, rooftop solar panels on buildings with lower heights are likely to have positive mean panel force coefficients due to the flow reattachment over roofs.